An Important Role in Novel Immune Mechanism and Diagnostic Model of Ankylosing Spondylitis: The CeRNA-ADRB2 Network - Huang F; Su Z; Yu C (Dove Medical Press, 2023)
Feihong Huang,1,2,* Zhiping Su,3,* Chaojie Yu1 1Department of Bone and Soft Tissue Surgery, Guangxi Medical University Cancer Hospital, Nanning, People's Republic of China; 2Spine and Osteopathy Ward, The First Affiliated Hospital of Guangxi Medical University, Nanning, People's Republic of China; 3Department of Radiation Oncology, Guangxi Medical University Cancer Hospital, Nanning, People's Republic of China*These authors contributed equally to this workCorrespondence: Chaojie Yu, Guangxi Medical University Cancer Hospital, Department of Bone and Soft Tissue Surgery, Guangxi Medical University Cancer Hospital, Nanning, Guangxi Zhuang Autonomous Region, 530021, People's Republic of China, Email h2021020@sr.gxmu.edu.cnObjective: The mechanism of ankylosing spondylitis (AS) remains unclear, and clinical diagnosis still pose challenges. This study aims to explore potential regulatory mechanisms underlying AS and develop a novel diagnostic model.Methods: Interspinous ligament (ISL) tissues were collected from control samples and ankylosing spondylitis with kyphotic deformity (AS-KD) samples during surgery, followed by high-throughput sequencing. By integrating gene expression profiles from publicly available AS peripheral blood (PB) samples, differentially expressed immune genes (DEIRGs) were identified. Through gene set enrichment analysis(GSEA), gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses, the regulatory mechanisms of the immune gene family in AS were explored. A diagnostic model for AS were constructed and validated it externally. Additionally, a competing endogenous RNA(ceRNA)-protein regulatory network was built for key immune genes.Results: Adrenergic receptor beta 2 (ADRB2) was downregulated in both ISL and PB samples. It was enriched in common pathways, including natural killer cell-mediated cytotoxicity, B cell receptor signaling pathway, Th1 and Th2 cell differentiation. Using the LASSO algorithm, 12 DEIRGs were identified, including the downregulated ADRB2. Based on the DEIRGs family, a novel diagnostic model was constructed with an AUC of 0.87 for the validation set and 0.7 for the test set. The AUC for ADRB2 alone was 0.75. Subgrouping AS based on these immune genes revealed a close association with neutrophils. GSEA and KEGG analysis of ISL, PB, and subgrouping of AS showed that ADRB2 may be involved in regulating the T cell receptor signaling pathway. Immune infiltration analysis indicated a decrease in CD8+ T cell infiltration, which was positively correlated with ADRB2. ADRB2 in AS-KD was regulated by multiple ceRNA-protein (lncRNA-[hsa-miR-513a-5p]-mRNA-protein).Conclusion: The immune gene family, especially ADRB2, participates in the mechanism and contributes to the diagnosis of AS.Keywords: ankylosing spondylitis, immune genes, adrenergic receptor beta-2, ADRB2, diagnostic model, competing endogenous RNA network, ceRNA network